2021
DOI: 10.1002/mame.202100032
|View full text |Cite
|
Sign up to set email alerts
|

Review on Shielding Mechanism and Structural Design of Electromagnetic Interference Shielding Composites

Abstract: Conductive polymer composites (CPCs) for electromagnetic interference shielding have received significant attention and shown rapid development. According to the electromagnetic wave interface conduction theory of Schelkunoff, excellent conductive performance and perfect conductive network structure are prerequisites for high shielding efficiency of electromagnetic interference shielding composites. Effective multiple interface reflection absorption, dielectric loss, and hysteresis loss characteristics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(61 citation statements)
references
References 93 publications
0
61
0
Order By: Relevance
“…Studies were conducted on several nanomaterials, such as ferromagnetic element nanoalloys, metal oxides, ferrites and their polymers and ICP-based nanocomposites in EMI shielding applications. 276–405 The choice of magnetic materials-filled ICP nanocomposites in EMI shielding applications is mainly guided by the dielectric loss, magnetic loss and impedance matching of the component(s) of the material(s) under investigation. It provides a combination of magnetic nanoparticles and ICPs that account for its additionally reduced weight, cost, enhanced flexibility and corrosion resistance, tuneability conductivity and tailorable permeability.…”
Section: Magnetic Nanomaterialsmentioning
confidence: 99%
“…Studies were conducted on several nanomaterials, such as ferromagnetic element nanoalloys, metal oxides, ferrites and their polymers and ICP-based nanocomposites in EMI shielding applications. 276–405 The choice of magnetic materials-filled ICP nanocomposites in EMI shielding applications is mainly guided by the dielectric loss, magnetic loss and impedance matching of the component(s) of the material(s) under investigation. It provides a combination of magnetic nanoparticles and ICPs that account for its additionally reduced weight, cost, enhanced flexibility and corrosion resistance, tuneability conductivity and tailorable permeability.…”
Section: Magnetic Nanomaterialsmentioning
confidence: 99%
“…In the early stages, CO 2 -blown cellular foams were produced by batch foaming and were primarily used in research and development . Later, semicontinuous and continuous processing techniques like microcellular injection and extrusion methods were developed to make lightweight foam components with multimaterials for mass production in industries for commercial applications like sofa cushions. , Eventually, the application of these polymeric foam is extended to the field of scaffold manufacturing, sensor, and electromagnetic shielding (EMI) …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Eventually, the application of these polymeric foam is extended to the field of scaffold manufacturing, sensor, and electromagnetic shielding (EMI). 10 Additive manufacturing can create prototypes and end products by developing new materials or improving the existing ones. 11 This technology has allowed the production of polymeric foam with hierarchical cellular structures by direct printing or assisted with other techniques.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, lots of researches have suggested that constructed structure of the EMI shielding materials (e.g., nacred, segregated, and porous structures) play an essential factor on their EM pollution shielding capacity. [17][18][19] However, there are still rare reports to compare the EMI shielding capability with different structure. In particular, nacred structure has been proven to be highly efficient to combine the exceeding advantages from each individual material.…”
Section: Introductionmentioning
confidence: 99%